Chemokines impact in Alzheimer’s disease - Domingues, Catarina de Barros Pinto Salvador (2018)
Alzheimer’s Disease (AD) is a neurodegenerative disorder neuropathologically characterized by the presence of extracellular senile plaques, intracellular neurofibrillary tangles and synaptic loss. Neuroinflammation has been associated with some neurodegenerative diseases, such as AD. In AD, increased Aβ production and aggregation, have a fundamental role in the activation of the inflammatory process. In turn, this could be fundamental in the early stages of this pathology, regarding the Aβ clearance and brain protection. However, chronic inflammation leads to an increase of the inflammatory mediators, such as cytokines, released by activated microglia, astrocytes, and neurons. The excessive production of these inflammatory components promotes alterations in both amyloid precursor protein (APP) expression and processing, stimulating the increase of Aβ accumulation and abnormal tau phosphorylation. This results in neurotoxic effects, irreversible damage and neuronal loss. Chronic inflammation is a feature of AD however, little is known about the effects of some chemokines on its pathogenesis. Thus, the main aim of this thesis was to study the impact of the interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) on apoptosis, APP and tau. The both studied chemokines resulted in small alterations regarding the cytotoxicity on SH-SY5Y differentiated cells, being a significant increase in apoptosis observed only for the MCP-1 at the highest concentration. For the APP processing no significant differences were obtained, although a tendency to increase at different concentrations and periods was registered for both IL-8 and MCP-1. With respect to tau and other cytoskeleton-associated proteins, it was possible to observe a tendency to increase in the phosphorylated residue (Ser396) at the higher concentrations, as well as alterations on actin and tubulin with an increase on acetylated-α tubulin. This effect can be translated by neuronal architectural and survival alterations. Therefore additional studies could contribute to a better understanding of the way that these chemokines act on AD pathogenesis.